2008
DOI: 10.2113/gssgfbull.179.2.195
|View full text |Cite
|
Sign up to set email alerts
|

The Neogene Veracruz fault: evidences for left-lateral slip along the southern Mexico block

Abstract: Structural data combined with analysis of satellite images and seismic profiles show that a major left-lateral strike-slip fault affects the Veracruz basin and post-5 Ma volcanic rocks of the Los Tuxtlas volcanic field (LTVF). The main volcanic alignment of the LTVF is located along this fault. Additional structural data collected in the Trans-Mexican volcanic belt (areas of Xalapa, Teziutlán and Huauchinango) show that the shear zone affects Pliocene Trans-Mexican volcanic rocks. Low seismicity associated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 33 publications
3
24
0
1
Order By: Relevance
“…This neotectonic feature could be the eastern boundary of the alleged South Mexican Block. The locations of the earthquakes of 1959, 1967 and 2009 roughly coincide with the fault trace proposed by Andreani et al (2008). Moreover, their focal mechanisms suggest a slight strike-slip component that could be related with the strike-slip motion of the Veracruz Fault.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This neotectonic feature could be the eastern boundary of the alleged South Mexican Block. The locations of the earthquakes of 1959, 1967 and 2009 roughly coincide with the fault trace proposed by Andreani et al (2008). Moreover, their focal mechanisms suggest a slight strike-slip component that could be related with the strike-slip motion of the Veracruz Fault.…”
Section: Discussionsupporting
confidence: 70%
“…Suárez and López (2011) López (2011) neither accepted nor rejected that all these events (including that of 1959) have a same tectonic origin. Andreani et al (2008), using PEMEX seismic profiles, digital elevation models, satellite imagery and field observations, proposed the existence of a major left lateral fault, calling it Veracruz Fault (Figure 2). This neotectonic feature could be the eastern boundary of the alleged South Mexican Block.…”
Section: Discussionmentioning
confidence: 99%
“…4c and d) have attempted to explain both the eastward escape of the Caribbean Plate as described by Lyon-Caen et al (2006) and tectonics of the Sierra Madre de Chiapas. Andreani et al (2008b) suggested a connection between the strike-slip faults of Chiapas; the Veracruz shear zone, which affects the Veracruz Basin further north; and the transtension of the Mexican volcanic arc (Fig. 4c).…”
Section: Models Of the Triple Junctionmentioning
confidence: 99%
“…A blue solid line represents the Chiapas State. Red lines within the TMVB outline the TCFS, and their locations were extracted from Andreani et al (2008). The abbreviations shown in the map are TMVB, Trans Mexican Volcanic Belt; MCVA, Modern Chiapanecan Volcanic Arc; MSMA, Miocene Sierra Madre Arc; CAVA, Central American Volcanic Arc; TCFS, Tula‐Chapala Fault system.…”
Section: Introductionmentioning
confidence: 99%